2022
DOI: 10.1002/fsn3.2836
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and hepatoprotective effects of novel heteropolysaccharide isolated from Lobularia maritima on CCl4‐induced liver injury in rats

Abstract: The aim of the present study was to investigate the extraction and the characterization of a novel heteropolysaccharide from Tunisian halophyte Lobularia maritima (LmPS). We were also interested in its antioxidant, anti‐inflammatory, and hepatoprotective effects on carbon tetrachloride (CCl4)‐induced liver injury in rats. LmPS physicochemical properties were evaluated by thin‐layer chromatography (TLC), high‐performance liquid chromatography (HPLC), thermogravimetric analysis (TGA), and UV absorption. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 72 publications
2
26
0
Order By: Relevance
“…PSLm was previously extracted from the aerial parts of L. maritima , presenting high percentage of carbohydrates (~85%) and the estimated average molecular weight was 130.62 kDa [ 62 ]. Total uronic acids were estimated by m-hydroxydiphenyl (MHDP) assay [ 63 ] using D-glucuronic acid as standards.…”
Section: Methodsmentioning
confidence: 99%
“…PSLm was previously extracted from the aerial parts of L. maritima , presenting high percentage of carbohydrates (~85%) and the estimated average molecular weight was 130.62 kDa [ 62 ]. Total uronic acids were estimated by m-hydroxydiphenyl (MHDP) assay [ 63 ] using D-glucuronic acid as standards.…”
Section: Methodsmentioning
confidence: 99%
“…The study showed a signi cant increase in lipid peroxidation in the heart of rats exposed to noise. These results can be explained by the increase of reactive oxygen species (ROS) production due to noise exposure [39,40]. On the other hand, our results showed a signi cant increase in catalase and SOD activities of rats exposed to 85 dB (A) sound level.…”
Section: Discussionmentioning
confidence: 53%
“…A probability value of p < .05 was considered as significant level. The values of analyzed data were expressed by mean ± SEM (Ben Hsouna et al, 2022).…”
Section: Discussionmentioning
confidence: 99%